PERBEDAAN PH SALIVA ANTARA ANAK YANG MINUM SUSU DENGAN KUMUR LARUTAN BAKING SODA DENGAN MINUM SUSU TANPA KUMUR LARUTAN BAKING SODA PADA SISWA SD GEDAWANG SEMARANG - Prasko ,; Bambang Sutomo; Sulur Joyo Sukendro (Jurnal Kesehatan Gigi, 2014)
ABSTRACT One of the factors that influence caries process is saliva, among the food products that can enhance the acid product is milk. Salivary pH can be increased by the use of a solution of baking soda. Objective to determine differences in salivary pH between children who drink milk with a solution of baking soda rinse with mouthwash to drink milk without a solution of baking soda.Types of research using descriptive method with cross sectional approach, the research will be conducted by a quasi-experimental. The population is a fifth grade elementary school students Gedawang 02 Semarang as many as 28 people. All the population sampled, and then divided into two groups randomly, which consists of: the intervention group without baking soda as many as 14 people, and groups with baking soda mouthwash for 14 people. Quantitative analysis inferential statistical test independent t- test with 95% confidence level (α = 0.05).The results showed there were differences in the pH of saliva between milk drinking group with a solution of baking soda mouthwash and gargle solution without baking soda. The state of saliva pH children who drink milk with a solution of baking soda mouthwash on a Class V student elementary Gedawang 02 Banyumanik Semarang with an average of 7.58. While no solution of baking soda rinse average 7.32 Conclusion salivary pH significantly different between children who drink milk with a solution of baking soda rinse with mouthwash to drink milk without a solution of baking soda in a Class V student elementary Gedawang 02 Banyumanik Semarang, appropriate statistical test results independent t test with a value of (p value = 0.043), p value a. It is recommended to the students to be able to choose an alternative material that can raise the salivary pH towards the base, one of which is by rinsing with a solution of baking soda concentration of 1%. Key words : salivary pH, Milk, Baking Soda Mouthwash Solution